Pembelajaran Kewirausahaan dalam Peningkatan Minat Berwirausaha di Kalangan Mahasiswa Universitas Adzkia - Juli Adevia; Relifra; Oza Syafriani; Nora Damayanti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Entrepreneurship education can be an effective strategy and play a crucial role in introducing and fostering entrepreneurial interest among students, aiming to provide them with practical experience. The purpose of this study is to examine the impact of entrepreneurship education on the entrepreneurial interest of students at Universitas Adzkia. This research employs a quantitative method with simple linear regression. Primary data collection was carried out by distributing questionnaires to 93 respondents. The results indicate a significant and positive influence of entrepreneurship education on the entrepreneurial interest among students of Universitas Adzkia. Various aspects of entrepreneurship education, including a comprehensive curriculum, practical experience, and mentorship support from lecturers, and how each of these aspects contributes to increasing entrepreneurial interest, are explored